A review on developing critical thinking skills through literary texts - Ahmad Shukri, Noraini; Mukundan, Jayakaran (Australian International Academic Centre, 2015)
Many ESL instructors are generally in agreement with the belief that it is essential that students should be assisted in developing critical thinking skills while being engaged in their language learning process especially those learning the target language at higher level (Stern, 1985; Dickinson, 1991; McKay, 2001; Terry, 2007; Van, 2009; Odenwald, 2010). As it enables language learners to engage in a more purposeful and self-regulatory in judgment, helping them in their evaluation of the arguments of others and of their own, coming to well-reasoned resolutions to any complex problems and to be able to resolve conflicts encountered in their daily lives. Critical thinking requires them to be actively involved in their own learning process as they attempt to individually understand and apply the information they are exposed to during the classroom interaction (Landsberger, 1999; Tung & Chang, 2009). The many advantageous and feasibility of teaching instruction that incorporates the study of literature in the ESL classroom which suggests that literature texts, if correctly chosen and instructed, can prove to be beneficial to ESL students’ overall level of literacy and critical thinking skills. Numerous empirical researches also asserted that literary texts that are authentic, enjoyable, and motivating would naturally increase both their knowledge of the target language patterns and cultural awareness.